Consultoria técnico-legislativa em políticas sociais no âmbito das Câmaras Municipais - Fantucci, Simone (2013)
The central theme of this work is the technical and legislative consulting activity in City Councils. Based on the knowledge of the assignments and work processes of a team of consultants, this study sought to answer what would be the contributions of Social Work in this professional acting space. It is known that advisory and consulting are listed as professional skills of a social worker in the Law that regulates the occupation, which led to the question: For what reasons has the existence of social worker consultant, acting with their technical and scientific knowledge within the scope of the Legislative Power, been rare? Assuming that the social worker has legitimate technical and professional competence to carry out legislative consulting, the following assumptions have been identified: the fact of there being a small number of and/or there being no social worker consultants in the Legislative Power would be associated with the fact that technical and legislative consulting has been consolidated recently and in Legislatives with greater structural complexity; the dilemmas about the meaning of a "highly technical" body of professionals in the Legislative Power are still persistent, such as the Institutional Consulting, due to several political interests; contests for the access to a consultant position are performed in different ways; there is low investment in human resources for the work linked to social areas; the Social Work profession would still be associated only with the Social Assistance area and the final execution of that Policy; and last but not least, the social workers little knowledge or total lack of knowledge of institutional legislative consulting. The research is qualitative and has been carried out through the search of documentary sources, bibliographical survey and gathering and analysis of statements by some legislative consultants who deal with social issues. As a result, we can say that the existence and the activity of Legislative Consulting are still incipient due to countless reasons, the main one being the little appreciation of the technical and scientific work. Moreover, Social Work has wide space for performance in this position, in a critical and relatively autonomous way, according to the ethicalpolitical project of the professional category of social workers, based on the Code of Ethics, which, together with other documents, sets out the principles, values and guidelines of the aforementioned project